DECISSION SUPPORT SYSTEM DI AMERIKA: SEBUAH EKISTENSI GLOBAL DAN MASADEPAN - Novia Ratnasari; Dhani Wahyu Wijaya; Akrom Tegar Khomeiny; Aji Prasetya Wibawa (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
The Industrial Revolution in America was influenced by technological development to become a highly developed country. Information technology combined with the Decision Support System (DSS) is able to give a new face to the application of technology in several fields, including: 1). Industry; 2). Health; 3). Agriculture; 4). Living environment ; 5). Military; and 6). Education. DSS was known in 1970 due to limitations in the development of technology for the military field. However, gradually the development of DSS can be applied in several fields. In this study using the Systematic Literature Review method with 4 stages of research, including: a). Research Questions; b). Inclusion Criterl; c). Identification of Papers; and D). Conclusions are carried out by grouping according to categories in certain years, including: 1). 1980-1990; 2). 1990-2000; 3). 2000-2010; and 4). 2010-2020. This research outlines an analysis of how the development of the use of DSS in various fields from year to year in America can be used as a policy maker and evaluating the use of technological trends in several fields. The results of this study are. The conclusion of this research is the field of industry and the health field is more dominant in use in the decision support system. Because the decision support system is very needed in the field. And as the time goes by, the use of the decision support system is increasingly reduced, even in the year 2010 to 2020, the use of a decision support system is called as artificial intelligence. Because artificial intelligence technology includes a decision support system in it. And artificial intelligence has a broader meaning is not merely a decision support system.